If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5X + -5 + -40 = 4X + -16 Reorder the terms: -5 + -40 + 5X = 4X + -16 Combine like terms: -5 + -40 = -45 -45 + 5X = 4X + -16 Reorder the terms: -45 + 5X = -16 + 4X Solving -45 + 5X = -16 + 4X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-4X' to each side of the equation. -45 + 5X + -4X = -16 + 4X + -4X Combine like terms: 5X + -4X = 1X -45 + 1X = -16 + 4X + -4X Combine like terms: 4X + -4X = 0 -45 + 1X = -16 + 0 -45 + 1X = -16 Add '45' to each side of the equation. -45 + 45 + 1X = -16 + 45 Combine like terms: -45 + 45 = 0 0 + 1X = -16 + 45 1X = -16 + 45 Combine like terms: -16 + 45 = 29 1X = 29 Divide each side by '1'. X = 29 Simplifying X = 29
| 3(2x-1)+3=2(x-5) | | 2x^4-2x^3+4x^2+3x-7=02 | | 3(4y-9)=12 | | 12(x-1)=6x+36 | | x^5+x^4-2x^3+4x^2+3x-7=0 | | x^500+7=0 | | x/18+=-2 | | 5-2x-8x-7=8-8x | | 5x-3y= 56 | | 4x-24=-2x+6 | | C+9=2c+5 | | y-7=3(x-4) | | 4y=-9x+10 | | 4+6s-1=7s+15-5s | | (2x-1)=x+3 | | 3x+5x-2p+4p= | | 10y+5x=25 | | -11+3x+4=17 | | -7x-8y=12 | | 0=-4 | | 4-4b=8(8+2b) | | x^2-(4p+1)x+(5p^2+2p)=0 | | y=296+7x | | y=7x+296 | | 3(w-2)+7=1-3w | | 4+v=3v-8 | | X=2(0) | | (-5)-(-2)=g+4 | | -60=6x-5y | | 34:4= | | -3(12-6x)=7(8-2x) | | (-35)=c+(-18) |